Recurrent pseudomonas septic arthritis. Issue 818 (December 1993) - Vickers, M. H.; Price, T.
Abstract : Episodes of septic arthritis caused by Pseudomonas aeruginosa occurred in a patient with an infected vascular graft. He responded well to antibiotic therapy and removal of the graft was not required. The aetiology of this unusual cause of septic arthritis is discussed.